Perancangan Media Pembelajaran Scrapbook Digital pada Materi Sistem Informasi Geografi untuk Peserta Didik Kelas X SMA - Yayuk Septiani Kunai; Fitryane Lihawa; Sri Maryati (-, 2026)
This study aims to design scrapbook digital learning media for Geographic Information Systems (GIS) material for tenth-grade senior high school students. The study focused on the media design stage through needs analysis, media structure design, visual element development, learning video selection, and interactive evaluation design. The analysis showed that GIS material contains abstract concepts, such as spatial data, attribute data, raster data, vector data, GIS components, and GIS applications, which require visual and interactive presentation. The media was designed using Canva in the form of a digital book that integrates text, images, illustrations, icons, colors, concept maps, learning videos, and QR code-based evaluation through Wayground. The media consists of a cover, foreword, table of contents, learning objectives, concept map, learning materials, videos, evaluation, glossary, and references. This design is expected to become an attractive, accessible, and visual alternative for Geography learning media that supports students’ understanding of basic GIS concepts in accordance with current digital learning needs.